Peningkatan Literasi Halal Melalui Sosialisasi Sertifikasi Produk Halal Bagi Masyarakat Desa Menjangan - Liani, Ani; Muslimah, Muslimah; Fadilah, Naila; Nurrahma, Emilla Dwi; Khasana, Uswatun; Rizqina, Saela; Kuriawan, Muhammad Reza (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
Low literacy regarding Halal Product Assurance regulations and the perception that obtaining a certificate requires expensive fees are the main obstacles for the community and micro-business actors in the MIS Menjangan environment, Bojong District. In fact, halal certification is a crucial regulatory obligation to ensure product quality. This community service aims to provide education regarding the urgency and procedures for halal certification registration, specifically through the self-declare scheme. The method of implementation is carried out through socialization, interactive discussions, and simulation of using the SIHALAL application. The results of the activity showed a significant increase in participants' understanding of the difference between halal and haram ingredients and the easy and free registration flow through the SEHATI program. This activity succeeded in changing the participants' mindset, building legal awareness, and motivating business actors to immediately register their products to increase economic value and implement a halal lifestyle.